P27 - Procalcitonin kinetics after burn injury and burn surgery in septic and non-septic patients: A retrospective observational study (Journal of Statistics on Health Decision, 2019)
IntroductionEarly sepsis diagnosis is of the utmost importance for the correct management of burn patients, because of its marked impact on outcomes and survival [1]. However, the systemic inflammatory response (SIR) triggered by burns mimics sepsis presentation and complicates its early diagnosis [2]. Biomarkers and their kinetics may aid this differentiation [3]. Serum procalcitonin (PCT) is one of the most studied biomarkers and exhibits fair accuracy and good correlation with sepsis severity [4]. Nevertheless, few studies have evaluated the perioperative changes in PCT levels in burn patients, and its utility in burn patients has been questioned due to an alleged high-rate of false-positives [5]. The present study evaluated the PCT kinetics utility in distinguishing sepsis from SIR during the first days after burn injury and after subsequent surgical interventions. MethodsStudy planThis was a retrospective observational study of all burn patients admitted to the Coimbra’s Burns Unit (Portugal) between January 2011 and December 2014 who presented with a total burn surface area (TBSA) ≥ 15% and who underwent subsequent surgery. A total of 145 patients were included in the analysis. Sepsis was diagnosed according to American Burn Association criteria. PCT kinetics were investigated a) during the first five days after burn injury and b) preoperatively and during the five days after surgery in three subsets of patients, including those with no preoperative and no postoperative sepsis (NN), no preoperative but postoperative sepsis (NS), and preoperative and postoperative sepsis (SS). Statistical analysisQualitative variables (gender and mortality) were described as counts and quantitative variables (age, TBSA and ABSI - Abbreviated Burn Severity Index) as the means and standard deviations. The number of surgical interventions and PCT values were described as medians and interquartile ranges (IQR). Comparisons between sepsis and non-sepsis groups were performed using Fisher’s exact test for qualitative variables and Mann-Whitney U test for quantitative variables. Friedman’s test was used for time comparisons of PCT levels. To evaluate the discriminatory power of PCT levels on consecutive days, receiver operating characteristic (ROC) curves and comparative analysis of the area under the curve (AUC) were performed. Kruskal Wallis test was used for the comparison of PCT kinetics between the three subgroups of perioperative patients and Mann-Whitney U test with Bonferroni correction for multiple comparisons of the specific pairs. A p-value ≤0.05 was considered significant. ResultsThe ABSI score, TBSA and mortality were higher in the patients who developed at least one sepsis episode [n=60] compared to the non-sepsis group [n=85] (p1.00 ng/mL were clearly associated with sepsis (p